Pengucapan Kosakata Bahasa Arab bagi Penutur Bahasa Sunda - Dea Selviana Novita Ali (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
At present there are so many languages ​​that we can know in this world, whether in the form of international languages ​​or even national languages. It is undeniable that Indonesia is a country that has many regional languages. In addition, as speakers of language, we rarely know the elements that exist in languages ​​such as phonetic studies. Because phonetics is one part of linguistic learning that studies various language sounds in general, and does not pay attention to meaning that is not functional. But in the application of linguistics at this time there are still many people who do not know the important elements in languages ​​such as phonetics especially in the study of phonetic Arabic. In addition, the relationship between Arabic and regional languages, namely Sundanese language which is very interesting to study, how the interrelation of the local language pentur in speaking Arabic which is a foreign language for their circles even though Arabic is one of the characteristics of the language of Muslims. The nature of this research is descriptive qualitative by analyzing data and using library research using trusted books and journals. This research can produce a phonetic learning of Arabic with speakers of regional languages ​​that have a distinctive dialect that is collaborated with Crowly's theory. Keywords: Language, Crowly, Phonetic